MARKET INSERTION OF FOREST COMMUNITIES IN SOUTHEASTERN MEXICO: THE RELEVANCE OF FOREST ENDOWMENT AND ORGANIZATION - Forster, R.A.; Guemes-Ricalde, F.J.; Zapata, J.L. (European Scientific Journal, ESJ, 2014)
In Mexico,rural communities own more than 80% of the total forest area, but less than 30% of these communities are involved in forest management activities. It has been shown that markets represent a critical incentive for the development and consolidation of community forestry. Despite that, little is known about the factors that enable certain communities to successfully insert into markets and prevent others from doing so. This paper examines factors that enable communities to insertin markets. The focus lies in two important community-specific variables: forest endowment and community organization. Information on market insertion was gathered through a survey of fifty-three communities in southern Quintana Roo, Mexico. The survey was complemented with expert interviews and the use of Geographic Information Systems (GIS). Findings indicate that forest endowment strongly determines market insertion. Community organization seems to have a reinforcing relation with market insertion, thus not allowing for unilateral causality. Among other aspects, the results indicate the existence of high market entry barriers to enter forest production and marketing, such as costly legal preconditions.